Effect of reduction of aggregate size on the priming effect in a Mollisol under different soil managements. (27th May 2019) - You, M.; Han, X.; Chen, X.; Yan, J.; Li, N.; Zou, W.; Lu, X.; Li, Y.; Horwath, W. R.
Summary: The priming effect (PE) is influenced by the amount and quality of soil organic carbon (SOC) held in different soil aggregates sizes. We examined the PE in Mollisols managed for >30 years as a grassland, farmland and bare fallow with 51, 32 and 27 g of SOC kg −1 soil, respectively, in a 60‐day incubation. Grassland soil contained 75% of aggregates in the macro size fractions >0.25 mm compared to <32% in farmland and bare fallow. Farmland and bare fallow soils contained proportionately more micro size fractions. The effect of aggregate size on the PE was assessed by comparing soils with intact aggregates to those where macroaggregates were reduced to microaggregate size fractions. In the grassland soil, cumulative CO2 mineralization increased by 20% in the reduced aggregate‐size treatment with no effect on farmland or bare fallow soils. Substrate additions to examine the PE included 13 C‐glucose and 13 C‐alanine (0.4 g C kg −1 dry soil), and inorganic N (2 mg N kg −1 dry soil). The PE was in the order glucose > alanine > (NH4 )2 SO4 and was most intense at day 3 of the incubation. Aggregate‐size reduction did not affect the PE within soil management treatments regardless of substrate addition. Most of the CO2 produced was derived from SOC rather than substrate addition and peaked at day 3. There was an interaction between microbial biomass C and dissolved organic C on the PE in the grassland soil only. The results suggested that the PE is an intrinsic characteristic of soils that are more affected by available C than the SOC in different aggregate fractions. Highlights: The priming effect from added C substrates was examined in relation to aggregate size. Reducing macroaggregates to <0.25 mm increased CO2 production in a grassland but not agricultural Mollisol. The positive priming effect was proportionately reduced in soil dominated by macroaggregates. The priming effect is an intrinsic characteristic affected by C additions and less so by aggregate protected C.